Plasma parameters estimation in the non-self-sustained gas discharge with hollow anode - Misiruk, I.O.; Tymoshenko, O.I.; Taran, V.S. (Вопросы атомной науки и техники, 2018)
A simple global model was built for estimation of the plasma properties in the non-self-sustained gas discharge with hollow anode [2, 4]. The calculated results are compared with experimental data of probe measurements. The applicability and limitations of the model are discussed.